Three-cluster policy in the implementation of corporate social responsibility at Intercontinental Bali Resort - Putu Rian Arde Surya; I Ketut Budarma; I Gede Mudana (International Journal of Green Tourism Research and Applications, 2020)
Purpose: This research is to analyze the three-cluster policy in international, national, and local policy on corporate social responsibility (CSR) implementation at InterContinental Bali Resort.Research methods: The research method used is descriptive qualitative with juridical-normative analysis techniques.Results and discussion: The CSR implementation is related to three-cluster regulation analysis, as follows: do small things with great love, embrace the joy of giving, give a little, safe a life!, green living!, and IHG earth week. The implementation of CSR has an impact on the sustainability of the company.Conclusion: A company in carrying out its activities are not only on more financial factors such as profits or dividends but be based on social and environmental responsibility for the present and long term.